Queering Criminology - Dwyer, Angela; Ball, Matthew; Crofts, Thomas; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Queer criminological work is at the forefront of critical academic criminology, responding to the exclusion of queer communities from criminology, and the injustices that they experience through the criminal justice system. This volume draws together both theoretical and empirical contributions that develop the growing scholarship being produced at the intersection of 'queer' and 'criminology'. Reflecting the diversity of research that is undertaken at this intersection, the contributions to this volume offer a deeper theoretical and conceptual development of this field alongside empirical research that illustrates the continued relevance and urgency of such scholarship. The contributions consider what it means to be queering criminology in the current political, social, and criminological climate, and chart directions along which this field might develop in order to ensure that greater social and criminal justice for LGBTIQ communities is achieved. .
Keywords: Social sciences; Criminology; Critical criminology; Crime -- Sociological aspects; Sociology; Social sciences -- Philosophy; Sex (Psychology).; Gender expression; Gender identity; Social Sciences; Gender Studies; Critical Criminology; Crime and Society; Criminology & Criminal Justice; Sociology, general; Social Theory; Electronic books